Pengaruh Gerakan Literasi Sekolah Terhadap Minat Baca Siswa Di SMA Negeri 1 Ampek Angkek Kabupaten Agam - Shafira Awaluddin; Nurizzati Nurizzati (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
This study aims to describe the effect of the school literacy movement on student interest in reading at SMA Negeri 1 Ampek Angkek. The type of research used in the study is quantitative research. This research method uses descriptive research methods. The population in this study were XII MIPA 1, 2, and 3 students totaling 102 students. The sample withdrawal in this study was carried out using simple random sampling technique, so the sample in this study was 50 students. The data collection technique was carried out by distributing questionnaires to the research sample. Based on the results of the data analysis that has been described, the results obtained from this study are as follows. First, the school literacy movement has a significant influence on student reading interest in SMA Negeri 1 Ampek Angkek Agam Regency. While the significant value obtained is 0.000 <0.05, so Ha is accepted and H0 is rejected, which means that if the implementation of the school literacy movement is implemented properly and in accordance with existing procedures, students' interest in reading will grow by itself. Second, the simple linear regression test shows that the correlation coefficient of 0.631 is positive which means that the direction of the influence of the school literacy movement on student interest in reading is positive. This shows that the more the school literacy movement increases, the more it will affect the students' interest in reading. The percentage of the influence of the school literacy movement on.